ANALISIS KERENTANAN PANTAI BERDASARKAN COASTAL VULNERABILITY INDEX (CVI) DI PANTAI KOTA MAKASSAR - Sakka, Sakka; Paharuddin, Paharuddin; Rupang, Eunike (Hasanuddin University, 2014)
The vulnerability of Makassar coast was measured using parameters of Coastal Vulnerability Index (CVI). CVIvalue was determined using geomorphology, shoreline change, coastal slope, mean wave height, mean tidalrange, and relative sea level change parameters. The Makassar coast was divided into a numbers of cells, eachwith the length of 1 km and width of 0.5 kminto the sea. CVI values werecalculated for each cell and the coastalvulnerability wereclassifiedinto five categories: very low - low - medium - high - very high. The results show thatthe coastline with high to very high vulnerability index are located at the southern part of Makassar, while thenorthern coastline generally have low to moderate vulnerability. The CVI parameters which contributed to highsusceptibilitywere the coastal slope and the shoreline change parameters. Keywords: Coastal Vulnerability Index, coastal slope and shoreline change, Makassar.